2020
DOI: 10.1055/s-0040-1714682
|View full text |Cite
|
Sign up to set email alerts
|

A Characterization of Ophthalmology Residency Program Social Media Presence and Activity

Abstract: Objective To determine the presence and activity of ophthalmology departments associated with residency programs on social media platforms and the use of these social media platforms by residency applicants. Design Cross-sectional online assessment of ophthalmology training program departments' presence and activity on Facebook, Twitter, and Instagram. Participants A total of 120 accredited ophthalmology residency training programs and 498 ophthalmology residency applicants. Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 13 publications
0
14
1
Order By: Relevance
“…Evaluation of 120 formally accredited United States ophthalmology training programs significantly associated program ranking with use of social media: 80% of the 20 top‐ranked programs used Facebook, Twitter and/or Instagram versus 33% of lesser ranked programs 73 . One‐third of 159 applicants to the Bascom Palmer Eye Institute in 2019 to 2020 had used social media to evaluate residency programs during the application process, 73 and one‐half of 214 applicants to Pennsylvania State University Department of Ophthalmology in 2015 to 2017 reported that social media platforms—including Student Doctor Network (SDN) 74 —provided information that was helpful in guiding their preferences 75 . The latter survey indicated that applicants often did not find adequate information on program websites and would have liked more information distributed by social media, suggesting platforms are being under‐utilised in this area.…”
Section: Applications Of Social Media In Ophthalmic Education Trainin...mentioning
confidence: 99%
See 1 more Smart Citation
“…Evaluation of 120 formally accredited United States ophthalmology training programs significantly associated program ranking with use of social media: 80% of the 20 top‐ranked programs used Facebook, Twitter and/or Instagram versus 33% of lesser ranked programs 73 . One‐third of 159 applicants to the Bascom Palmer Eye Institute in 2019 to 2020 had used social media to evaluate residency programs during the application process, 73 and one‐half of 214 applicants to Pennsylvania State University Department of Ophthalmology in 2015 to 2017 reported that social media platforms—including Student Doctor Network (SDN) 74 —provided information that was helpful in guiding their preferences 75 . The latter survey indicated that applicants often did not find adequate information on program websites and would have liked more information distributed by social media, suggesting platforms are being under‐utilised in this area.…”
Section: Applications Of Social Media In Ophthalmic Education Trainin...mentioning
confidence: 99%
“…Evaluation of 120 formally accredited United States ophthalmology training programs significantly associated program ranking with use of social media: 80% of the 20 top-ranked programs used Facebook, Twitter and/or Instagram versus 33% of lesser ranked programs. 73 One-third of 159 applicants to the Bascom Palmer Eye Institute in 2019 to 2020 had used social media to evaluate residency programs during the application process, 73 and one-half of 214 applicants to State University Department of Ophthalmology in 2015 to 2017 reported that social media platforms-including Student Doctor Network (SDN) 74 provided information that was helpful in guiding their preferences. 75 The latter survey indicated that applicants often did not find adequate information on program websites and would have liked more information distributed by social media, suggesting platforms are being under-utilised in this area.…”
Section: Trainee Recruitmentmentioning
confidence: 99%
“…8 Of 120 ophthalmology residency programs evaluated, 37.5% had a Facebook page, 24.3% were on Twitter, and 18.3% had an Instagram page. 9 Among the ophthalmology residency programs ranked as top-20 by Doximity, 80% had at least one social media account compared to only 33% of the remaining programs. 9 Additionally, the top 20 programs had a greater social media following.…”
Section: Educating Doctoral Traineesmentioning
confidence: 99%
“…9 Among the ophthalmology residency programs ranked as top-20 by Doximity, 80% had at least one social media account compared to only 33% of the remaining programs. 9 Additionally, the top 20 programs had a greater social media following. 9 This study highlights that ophthalmology institutions are making an active effort to reach out to medical trainees via social media.…”
Section: Educating Doctoral Traineesmentioning
confidence: 99%
See 1 more Smart Citation